A cumulative meta‐analysis of the effects of individual physical activity interventions targeting healthy adults - Love, R. (Obes Rev, 2018)
Despite a large and increasing evidence base on physical activity interventions, the high rates of physical inactivity and associated chronic diseases are continuing to increase globally. The purpose of this cumulative meta‐analysis was to investigate the evolution of randomized controlled trial evidence of individual‐level physical activity interventions to asses if new trials are contributing novel evidence to the field. Through a two‐staged search process, primary studies examining the effects of interventions targeted at increasing physical activity within healthy adult populations were pooled and selected from eligible systematic reviews. Cumulative meta‐analyses were performed on effect sizes immediately post‐intervention (n = 62), and for long‐term behaviour change (≥12‐month post‐baseline; n = 27). Sufficiency and stability of the evidence was assessed through application of pre‐published indicators. Meta‐analyses suggest overall positive intervention effects on physical activity. The evidence base for effectiveness immediately post‐intervention reached levels of sufficiency and stability in 2007; and for long‐term follow‐up in 2011. In the time since, intervention effectiveness has not substantially changed, and further trials are unlikely to change the direction and magnitude of effect. Substantial evidence exists demonstrating that physical activity interventions can modify individual behaviour in controlled settings. Researchers are urged to shift focus towards investigating the optimization, implementation, sustainability and cost‐effectiveness of interventions.